Assessing essentiality of transketolase in Mycobacterium tuberculosis using an inducible protein degradation system. Issue 1 (4th August 2014) - Kolly, Gaëlle S.; Sala, Claudia; Vocat, Anthony; Cole, Stewart T.
Abstract Improved genetic tools are required to identify new drug targets in Mycobacterium tuberculosis. To this aim, genetic approaches, targeting either transcription and/or protein degradation, have been developed to appraise gene essentiality and to test the impact of gene silencing on bacterial survival. Here, we successfully combined the Tet‐Pip OFF system, which downregulates transcription through the TetR and Pip repressors, with SspB‐mediated protein degradation to study depletion of the transketolase encoded by the tkt (rv1449c) gene. We show that depletion of Tkt using the RNA silencing and protein degradation (RSPD) system arrested growth of M. tuberculosis in vitro faster than the Tet‐Pip OFF system alone. In addition, we extended the new combined approach to an ex vivo model of M. tuberculosis infection in THP‐1 cells. Tkt‐depleted bacteria displayed reduced virulence as compared to wild type bacilli, thus confirming the essentiality of the enzyme for intracellular growth.